2020
DOI: 10.18502/ijph.v49i3.3149
|View full text |Cite
|
Sign up to set email alerts
|

Specific Detection of Fasciola hepatica and F. gigantica in Infected Domesticated Animals Using High-Resolution Melting Analysis (HRM)

Abstract: Background: It is difficult to make an exact morphological distinction between Fasciola hepatica and Fasciola gigantica. We used High Resolution Melting analysis (HRM) method to differentiate the F. hepatica species from F. gigantica in order to differentiate them. Methods: Overall, 80 adult liver flukes were collected from infected slaughtered animals including cattle, sheep and goats from Lorestan Province, western Iran from Sep 2015 to Aug 2017. Genomic DNA was extracted using commercial DNA extraction kit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The HRM technique by targeting Cox1 is as a powerful, rapid and sensitive method to differentiate into Fasciola hepatica and F. gigantica in the northwest (Ardabil) and southeast (Zahedan) of Iran. Another study was conducted to detect F. hepatica and F. gigantica by HRM analysis of mDNA including Cox1 , Cox3 , and ND6 in western Iran and concluded that the method is simple, fast and reliable ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HRM technique by targeting Cox1 is as a powerful, rapid and sensitive method to differentiate into Fasciola hepatica and F. gigantica in the northwest (Ardabil) and southeast (Zahedan) of Iran. Another study was conducted to detect F. hepatica and F. gigantica by HRM analysis of mDNA including Cox1 , Cox3 , and ND6 in western Iran and concluded that the method is simple, fast and reliable ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…As this method is generally restricted to be used in the diagnosis of helminths species, it was specifically used in two studies carried out in northwest and west of the country to survey Fasciola spp. ( 13 , 26 ). Moreover, another study used HRM to diagnose Trichostrongylus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the expansion of molecular techniques in the 2000s added a new dimension to the screening of fasciolosis transmission. Molecular tools solve the parasitological method's drawbacks of sensitivity and specificity, allow to discriminate both Fasciola species and the hybrid forms in a reliable way and to characterize genetically the different parasite and host populations (Martínez-Valladares and Rojo-Vázquez, 2016; Amor et al ., 2020; Moghadamizad et al ., 2020).…”
Section: Scientific and Political Factors: Changing The View From Spomentioning
confidence: 99%
“…Different techniques within each type of non-classical detection method have been applied indistinctively in the monitoring of infection within definitive hosts such as ELISAs (Espino et al ., 1998), rapid immunochromatographic tests (Xifeng et al ., 2019), conventional PCR, loop-mediated isothermal amplification (Martínez-Valladares and Rojo-Vázquez, 2016) and high-resolution melting analysis (Moghadamizad et al ., 2020). In addition, detection of snail infections also evolved from the classical parasitological dissection to immunoenzymatic assays (Alba et al ., 2015 a ) and molecular methods (multiplex PCR, Alba et al ., 2015 b ; real-time PCR, Schweizer et al ., 2007; etc.).…”
Section: Scientific and Political Factors: Changing The View From Spomentioning
confidence: 99%